Acylation of soluble polysaccharides in a biphasic system catalyzed by a CE2 acetyl esterase. (1st May 2017) - Kanelli, Maria; Topakas, Evangelos
Highlights: A biphasic system was utilized for the regioselective transesterification reactions. Ct CE2 is capable of acylating soluble polysaccharides in an aqueous medium. Acylation degree varied from 0.022 to 1.083 mmolacy group *gpolysaccharide −1 . Monosaccharides acquired acylation yields from 11 up to 65%. Monoacylation was favored in disaccharides exhibiting yields from 23 up to 58%. Abstract: Within the last decade, acylated polysaccharides have drawn attention, since they find applications in numerous fields as biocompatible and biodegradable amphiphilic compounds. The ability of a CE2 acetyl esterase from Clostridium thermocellum to catalyze acyl transfer to β-glucan and manno-polysaccharides of significant interest was investigated. Initially, screening tests were conducted on aldohexose monosaccharides and disaccharides, exploiting the enzyme's strict regioselectivity at O -6 position. Modified monosaccharides acquired acylation yields from 11 up to 65%, showing preference for small chain acyl donors, while disaccharides exhibited conversion yields from 23 up to 58%, with preference to monoacylation. The transesterification reactions were carried out in two-phase mixtures consisted of water/vinyl esters. Acylation of polysaccharides were confirmed by TLC and FT-IR, while the degree of acylation was determined via an indirect method, estimating a range of acylation from 0.022 to 1.083 mmolacyl group *gpolysaccharide −1 depending on the structure and composition of the target polysaccharide.